Asmara Power Distribution and Rural Electrification Project : Pre-electrification Survey Analysis - O'Sullivan, Kyran; Fitzgerald, Kevin (World Bank, Washington, DC, 2013)
This report presents the findings and recommendations of a Pre-electrification Survey done in preparation for the Asmara Power Distribution and Rural Electrification Project. The survey was designed to characterize energy use in existing institutions, commercial enterprises and households before electrification and, thereby, set a baseline for monitoring and evaluation of the impacts of the project going forward. The report begins with a summary of the survey s main findings. It continues with an introduction describing the background of the project. Section 1 presents an estimation of electrification s benefits using the household survey data. Section 2 discusses recommendations for ongoing monitoring and evaluation of the project. An appendix follows.